Recuperare la scalarità del denso, tra resistenza e studying up - Simonicca, Alessandro (International Gramsci Journal, 2023)
The essay starts with Kate Crehan's reflection on Gramsci's contribution to anthropology and compares it with Sherry Ortner’s positions of 1995 and 2017 on the nature of anthropological ethnography. The proposal is to look at the anthropological “density”, in Geertz’s connotation, in terms of multiplicity of cultural identities, plural sources of knowledge and varied intersections of points of view, which cannot be attributed to a spatially “common sense” or to a unified political point of view.